Computer-Aided Surgical Simulation in Head and Neck Reconstruction: A Cost Comparison among Traditional, In-House, and Commercial Options - Li, Sean S.; Copeland-Halperin, Libby R.; Kaminsky, Alexander J.; Li, Jihui; Lodhi, Fahad K.; Miraliakbari, Reza (Journal of Reconstructive Microsurgery, 2018)
Background Computer-aided surgical simulation (CASS) has redefined surgery, improved precision and reduced the reliance on intraoperative trial-and-error manipulations. CASS is provided by third-party services; however, it may be cost-effective for some hospitals to develop in-house programs. This study provides the first cost analysis comparison among traditional (no CASS), commercial CASS, and in-house CASS for head and neck reconstruction.Methods The costs of three-dimensional (3D) pre-operative planning for mandibular and maxillary reconstructions were obtained from an in-house CASS program at our large tertiary care hospital in Northern Virginia, as well as a commercial provider (Synthes, Paoli, PA). A cost comparison was performed among these modalities and extrapolated in-house CASS costs were derived. The calculations were based on estimated CASS use with cost structures similar to our institution and sunk costs were amortized over 10 years.Results Average operating room time was estimated at 10 hours, with an average of 2 hours saved with CASS. The hourly cost to the hospital for the operating room (including anesthesia and other ancillary costs) was estimated at $4,614/hour. Per case, traditional cases were $46,140, commercial CASS cases were $40,951, and in-house CASS cases were $38,212. Annual in-house CASS costs were $39,590.Conclusions CASS reduced operating room time, likely due to improved efficiency and accuracy. Our data demonstrate that hospitals with similar cost structure as ours, performing greater than 27 cases of 3D head and neck reconstructions per year can see a financial benefit from developing an in-house CASS program.
Keywords: CASS; VSP; head and neck